ChemInform Abstract: Highly Regioselective Opening of Zirconacyclopentadienes by Remote Coordination: Concise Synthesis of the Furan Core of the Leupyrrins. Issue 20 (25th April 2013) - Debnar, Thomas; Dreisigacker, Sandra; Menche, Dirk
Abstract An efficient method for the highly regioselective opening of aliphatic zirconacyclopentadienes based on a novel concept of remote stereorelay is described.